The Acquisition of Meaning and Functions of Personal Pronouns - Balčiūnienė, Ingrida (Kalbotyra, 2005)
The aim of this article is to present the acquisition of personal pronouns and to compare this process in Lithuanian and English languages. The main attention is paid to the order of their acquisition, the formation of the meaning and functions. The pronouns I/aš and you/tu were one of the first structures acquired both in English and Lithuanian, and the formation of their meaning is similar. At the beginning of acquisition the same types of errors were observed: the substitution of a proper name for a pronoun and the reversal of 1st and 2nd person pronouns. Later, when children acquired the meaning and functions of participational personal pronouns they started to use them to refer the addresser and the addressee. The acquisition of non-participational pronouns was similar both in English and Lithuanian: children used them to refer mostly to inanimate objects. English speaking children acquired the pronoun it earlier than pronouns he/she. Lithuanian girl at first used the pronoun jis ‘he’ to refer inanimate object only.